Student Contributions to Improving Student Literacy and Numeracy in the Actualization of the Teaching Campus Program - Ilma Nur Hayati; Sabar Narimo (Ideguru: Jurnal Karya Ilmiah Guru, 2025)
This study aims to explain the program implemented to improve students' literacy and numeracy skills at SMP Negeri 3 Gondangrejo. The method used in this research is descriptive qualitative. The data obtained came from the implementation of the program to improve literacy and numeracy skills. The data collection process was done through observation and documentation. The results show that literacy and numeracy skills are very important for students to master since primary and secondary school levels, so that they can more easily understand the subject matter and as preparation for continuing education to a higher level. The programs implemented to improve these skills include book swap party, literacy day, reading corner, mathventure, science art project, library revitalization program, school mading, reuse art, smart learning workshop, and socialization of the three big sins in education.